Intelligent control for distributed smart grid: comprehensive system integrating wave, fuel cell, and photovoltaic power generation - B S, Manohar; Banakara, Basavaraja (Institute of Advanced Engineering and Science, 2025)
The intermittent supply from renewable energy sources reckons integration of different renewable sources that can provide robust and uninterrupted energy supply to the grid. This paper applies an intelligent control method to such hybrid power generation involving a wave generator, fuel cell, and solar power generator integrated into the distribution power grid. A common DC link that supplies the voltage source converter (VSC) is powered by the output from the hybridized wave, fuel cell and photovoltaic (PV) output. Wave generator uses the rectifier DC-DC converter, PV uses a maximum power point tracking (MPPT)-controlled DC-DC converter and fuel cell uses a DC-DC converter. All DC sources converge at the DC link, connecting to an inverter featuring another voltage source controller for controlled AC voltage. In instances of power unavailability from renewable resources, the fuel cell seamlessly provides power. The inverter controls the integration of power from these sources to the grid and maintains stable DC link voltage due to the dynamic nature of the DQ controller. MATLAB-based simulation is developed for the proposed controller and a comparison between both proportional integral and adaptive neuro-fuzzy inference system (ANFIS) controller in the DC link voltage regulation loop is observed. An ANFIS controller is employed as an alternative to the proportional integral (PI) controller and found that the ANFIS controller outperformed the PI controller in voltage regulation at the DC link.